2009
DOI: 10.1016/j.nima.2008.12.154
|View full text |Cite
|
Sign up to set email alerts
|

Progress in developing hybrid RPC: GEM-like detectors with resistive electrodes

Abstract: We have recently developed an innovative detector of photons and charged particles: a GEM-like gaseous amplification structure with resistive electrodes instead of commonly used metallic ones. This novel detector combines the best property of GEMs-the capability to operate in a cascaded mode and in poorly quenched gases -and of RPC: the protection against sparks. In this paper will shortly review our latest achievements in this direction, however the main focus will be given on a new advanced design that allow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Recently, several groups working with such detectors fully confirmed our earlier results [12]- [14]. Unfortunately, the position resolution of RETGEM (similarly to TGEM) is limited by the hole's diameter and pitch and is about 0.7-1 mm [15], [16].…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Recently, several groups working with such detectors fully confirmed our earlier results [12]- [14]. Unfortunately, the position resolution of RETGEM (similarly to TGEM) is limited by the hole's diameter and pitch and is about 0.7-1 mm [15], [16].…”
supporting
confidence: 64%
“…Unfortunately, as noted in the introduction, the position resolution of the RETGEM is quite modest (0.7-1 mm) [15], [16] due to the large hole's diameters and pitch.…”
Section: B Csi Coated Meshesmentioning
confidence: 99%
“…Inside each gas chamber, an S-RETGEM was installed with a drift mesh typically placed 2 cm above it. The concept and the design of the S-RETGEM are described in several recent papers [9,10]. Recalling the main features, it is a Thick GEM [11][12][13] with double-layered micro pattern electrodes with an inner layer consisting of thin Cu strips and an outer layer comprised of a resistive grid, manufactured by screen printing technology, on top of Cu strips.…”
Section: Detectors Designmentioning
confidence: 99%
“…At higher gains 55 Fe was used and the gain values were estimated from the measured avalanche charge and the known sensitivity of the amplifier. As it can be seen, at room temperature, the maximum achievable gain was ~3x10 4 which is 3-10 times higher than that achieved with other micropattern gaseous detectors operated in Ar. No feedback pulses originating from the CsI photocathode were observed (they should have a delay of a few μs) even at the maximum achievable gains, proving that in RMMDs the avalanche region is geometrically well shielded with respect to the photocathode.…”
Section: Resultsmentioning
confidence: 71%
“…Usually surface streamers appear if the field lines are parallel to the dielectric surface (along all the surfaces) between the anode and the cathode electrodes. At the last three RPC conferences [3][4][5], we reported that the resistive electrode approach, used in RPCs, can be successfully applied to micropattern gaseous detectors making them sparkprotected. Our first spark-protected detectors -GEM and MICROMEGAS -had unsegmented resistive electrodes [3,5].…”
Section: Introductionmentioning
confidence: 99%